POLITIK HUKUM PENANGANAN STUNTING DAN TANTANGAN MENUJU GENERASI EMAS INDONESIA 2045 - Andika, Hasyim Trio; Yusdiyanto, Yusdiyanto; Firmansyah, Ade Arif; Sujadmiko, Bayu; Zazili, Ahmad (Universitas Muhammadiyah Metro, 2025)
Stunting is a condition of growth failure caused by chronic malnutrition and recurrent infections during the first 1,000 days of life, which has a serious impact on the quality of Indonesia's human resources. Stunting is not only a health issue, but also a violation of children's rights guaranteed by the constitution and national legal instruments. In this context, the state has a legal responsibility to ensure every child's right to nutrition and health in a comprehensive manner. An analysis of Presidential Regulation No. 72 of 2021 shows that national regulations have established strategies to accelerate the reduction of stunting, but they lack mechanisms for sanctions, oversight, and clear delineation of authority. Weak cross-sectoral coordination, low legal literacy among the public, and minimal public participation undermine the effectiveness of policies. To enrich the analysis, this study highlights best practices from Malaysia, Myanmar, and Thailand. These countries have successfully reduced stunting rates through a multisectoral, community-based, and rights-oriented approach. Their strategies include nutrition education, food security, women's empowerment, and interventions based on educational and social institutions. Without a strong and implementable legal framework, and without learning from successful global practices, Indonesia will struggle to achieve significant reductions in stunting. Therefore, strengthening legal policies and adopting international best practices are crucial to realizing the vision of Indonesia's Golden Generation 2045